Dynamic entrepreneur board game using HTML5 / Siti Noraina Amira Jafri - Jafri, Siti Noraina Amira (2017)
Nowadays, game is the most popular entertainment especially among student such as digital board game. An existing digital board game is lack of dynamic in term of content thus the players feel bored after playing a game repeatedly because the game become unchallenging and familiar to them. This study aims to determine the applicability of dynamic content on board game. The dynamic board game is developed based on the entrepreneur environment by using HTML5. The data onboard is made dynamic by using JSON and stored in X ampp server. The 'Lot' will have a dynamic value where it will change based on the rolled dice. The player also can buy or ignore the 'Lot'. The 100 questionnaires were distributed to 100respondents in Faculty of Business, UiTM Shah Alam. The questionnaire is to determine the percentage of dynamism of dynamic board game in the related field. The result show that the objectives in this proposed project is met